Situation of Rabies in Iraq: A retrospective study 2006-2010 - Fathalla, Maral (University of Thi-Qar Journal of Science, 2012)
Rabies is a highly fatal viral zoonotic disease that is transmitted to human body via the saliva of infected mammals. It is endemic in Iraq especially in rural areas. A cross-sectional retrospective study was carried out in order to obtain 5 year analysis of rabies cases (2006-2010) in the zoonotic section of Center of Communicable Disease Control (CDC), Baghdad city during January 2011. All case records of diagnosed human rabies admitted in different Iraqi governorates hospitals were reviewed and then statistically analyzed. The results showed that the total number of registered rabies cases in Iraq during the included study period was equal to (106) cases, the highest number (27) cases was during the year (2009).The epidemiological profile of patients, showed the predominance of males(91) cases compared to females (15) cases. People at risk were children below ten years of age (35.8%). Distribution of rabies cases according to different Iraqi governorates was highest in Baghdad city (17.92%) and this was directly related to the highestnumber of dog bite victims (18.12%) also in Baghdad city, while the monthly distribution of registered rabies cases showed no evident seasonal variation.Recommendations was suggested for health education to increase awareness of people towards the problem, control of stray dogs and incorporate rabies control within the activities of primary health care activities.